Gastrointestinal symptoms and fecal shedding of SARS-CoV-2 RNA suggest prolonged gastrointestinal infection - Natarajan, Aravind; Zlitni, Soumaya; Brooks, Erin F.; Vance, Summer E.; Dahlen, Alex; Hedlin, Haley; Park, Ryan M.; Han, Alvin; Schmidtke, Danica T.; Verma, Renu; Jacobson, Karen B.; Parsonnet, Julie; et al. (Med (New York, N.Y. : Online), 2022)
COVID-19 manifests with respiratory, systemic, and gastrointestinal (GI) symptoms.1, SARS-CoV-2 RNA is detected in respiratory and fecal samples, and recent reports demonstrate viral replication in both the lung and intestinal tissue.2–4 Although much is known about early fecal RNA shedding, little is known about long-term shedding, especially in those with mild COVID-19. Furthermore, most reports of fecal RNA shedding do not correlate these findings with GI symptoms.5 We analyzed the dynamics of fecal RNA shedding up to 10 months after COVID-19 diagnosis in 113 individuals with mild to moderate disease. We also correlated shedding with disease symptoms. Fecal SARS-CoV-2 RNA is detected in 49.2% [95% confidence interval, 38.2%–60.3%] of participants within the first week after diagnosis. Whereas there was no ongoing oropharyngeal SARS-CoV-2 RNA shedding in subjects at 4 months, 12.7% [8.5%–18.4%] of participants continued to shed SARS-CoV-2 RNA in the feces at 4 months after diagnosis and 3.8% [2.0%–7.3%] shed at 7 months. Finally, we found that GI symptoms (abdominal pain, nausea, vomiting) are associated with fecal shedding of SARS-CoV-2 RNA. The extended presence of viral RNA in feces, but not in respiratory samples, along with the association of fecal viral RNA shedding with GI symptoms suggest that SARS-CoV-2 infects the GI tract and that this infection can be prolonged in a subset of individuals with COVID-19. This research was supported by a Stanford ChemH-IMA grant; fellowships from the AACR and NSF; and NIH R01-AI148623, R01-AI143757, and UL1TR003142. [Display omitted] •Approximately one-half of COVID-19 patients shed fecal RNA in the week after diagnosis•Four percent of patients with COVID-19 shed fecal viral RNA 7 months after diagnosis•Presence of fecal SARS-CoV-2 RNA is associated with gastrointestinal symptoms•SARS-CoV-2 likely infects gastrointestinal tissue Gastrointestinal symptoms and SARS-CoV-2 RNA shedding in feces point to the gastrointestinal tract as a possible site of infection in COVID-19. Researchers from Stanford University measured the dynamics of fecal viral RNA in patients with mild to moderate COVID-19 followed for 10 months post-diagnosis. The authors found that fecal viral RNA shedding was correlated with gastrointestinal symptoms in patients who had cleared their respiratory infection. They also observed that fecal shedding can continue to 7 months post-diagnosis. In conjunction with recent related findings, this work presents compelling evidence of SARS-CoV-2 infection in the gastrointestinal tract and suggests a possible role for long-term infection of the gastrointestinal tract in syndromes such as “long COVID.” Natarajan et al. perform a longitudinal study of fecal SARS-CoV-2 RNA shedding in patients with mild to moderate COVID-19, revealing that patients can shed RNA for up to 7 months after infection, that shedding is associated with gastrointestinal symptoms, and that the gastrointestinal tract may be infected even after the respiratory infection has cleared.